Integration of National Security and Rehabilitation in Sentencing for Perpetrators of Terrorist Crimes: Integrasi Keamanan Nasional dan Rehabilitasi dalam Penjatuhan Hukuman bagi Pelaku Tindak Pidana Terorisme - Didik Purnomo; Bagus Hendradi Kusuma (Indonesian Journal of Counter Terrorism and National Security, 2024)
This research analyzes the integration between national security interests and rehabilitation in the sentencing system for terrorists in Indonesia, focusing on how the legal framework, policies, and law enforcement practices can combine strict monitoring mechanisms in special correctional institutions with deradicalization and social reintegration programs. The research method relies on a document study of Law No. 5 of 2018 on the Eradication of Criminal Acts of Terrorism, the national action plan for counter-terrorism, as well as a comparative analysis of terrorism sentencing models in Malaysia and Singapore based on a literature review and secondary data. The research results indicate that Indonesia's regulations have adopted a balanced approach between security and rehabilitation by establishing special class correctional institutions and religious psychosocial-based deradicalization programs. However, its implementation is hindered by limitations in human resources, funding allocation, and a lack of post-release monitoring mechanisms. The recidivism rate remains significant despite cases of successful rehabilitation for inmates who receive adequate economic and psychosocial support. The research concludes that the effectiveness of counter-terrorism sentencing requires synergy between institutions, a multisectoral approach, and strengthening the capacity of rehabilitation infrastructure. Policy recommendations include revising the Anti-Terrorism Law to clarify mandatory rehabilitation clauses, enhancing the capacity of law enforcement human resources and correctional facility managers' capacity, and developing post-release economic and community-based reintegration programs.